THE IMPACT OF DIGITAL TRANSFORMATION ON FINANCIAL REPORTING AND ANALYSIS IN THE ACCOUNTING INDUSTRY - Xin Miaoquan; Kong Wei Yu; Liu Xuewen; Wang Yi; Yin Jun; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2023)
This research paper explores the impact of digital transformation on financial reporting and analysis in the accounting industry. Digital transformation has revolutionised how accounting professionals and firms operate, offering new possibilities and challenges. The paper begins by providing background information on digital transformation in the accounting industry and highlights the significance of studying its impact on financial reporting and analysis. The conceptual framework outlines the key components of digital transformation, including cloud computing, data analytics, automation, and integration of software systems. It further discusses how these components are adopted and integrated into the accounting industry, enabling enhanced efficiency, accuracy, and timeliness in financial reporting and analysis. The paper discusses the benefits and challenges associated with digital transformation. The benefits include improved data accuracy, real-time reporting, enhanced collaboration, and access to advanced data analytics. However, challenges such as data security, privacy concerns, and the need for upskilling the workforce are also examined. The paper concludes by predicting emerging trends in financial reporting and analysis with further digital transformation. It discusses the growing importance of advanced data analytics, real-time reporting, integration of APIs, and the adoption of blockchain technology. Facts support these trends and highlight the transformative potential of digital transformation.